Mixed clinical pictures of endogenous endophthalmitis in a relapse leukemic patient - Annuar Z Azmi; Sylves Patrick; Mohamad Israk Isa; Shuaibah Ab Ghani (Cureus, Inc., 2023)
Endogenous endophthalmitis is rare but sight-threatening in leukemic patients, which can have devastating sequelae. We report a case of a 15-year-old teenager with acute myeloid leukemia on relapse, presented with a mixed picture of endogenous endophthalmitis. The diagnosis dilemma in this patient proved difficult as Investigations and management can be challenging as young teenagers are usually less cooperative than adults. Endogenous endophthalmitis is not uncommon in this group of patients; however, mixed clinical pictures are almost unheard of, and the final diagnosis can be misleading if not treated accordingly. Viral infections such as cytomegalovirus (CMV), bacterial, and fungal are all considered potential opportunistic infections. Diagnosis of endogenous endophthalmitis is complex and relies heavily on the clinical characteristics of each organism supported by intravitreal tapping and culture samples. However, data from endogenous endophthalmitis in leukemic patients is scarce nowadays across the board. In this case report, we highlight the challenges of managing endogenous endophthalmitis in a young leukemic patient due for bone marrow transplantation. Future studies are needed to investigate the current microorganism trends and treatments available. An algorithm for managing endophthalmitis in immunosuppressed patients should be done to provide a better approach from the get-go.